Popliteal artery to tibial plateau distance at the knee level: a radiological study to assess injury risks in osteoarthritic knees using dual source dual energy CT scan - Abd Rahim, Ezamin; Abu Hassan, Hasyma; Suppiah, Subapriya; Mohamad Saini, Suraini; Abdullah, Arifaizad; Hussin, Paisal; Mohd Nasir, Mohd Nizlan; Ahmad Sidique, Shaufique Fahmi; J., Hariati (Universiti Putra Malaysia Press, 2017)
Popliteal artery injury is the most disastrous intraoperative complication during total knee replacement. This study aims to determine the mean distance between the popliteal artery (PA) and the tibial plateau in normal and osteoarthritic patients who underwent Dual Energy CT Angiography (CTA) of the lower limb. Materials and Methods: All CTA lower limb examinations from January 2013 to October 2014 were retrospectively reviewed. The distance between the PA the tibial plateau distance and the thickness of popliteus muscle were electronically measured. We used modified Kellgren and Lawrence's Classification to grade the osteoarthritis in patients who underwent CT examinations regardless of symptoms. Results: There were a total of 126 patients who underwent CTA (93 males and 33 females). 54 of them were Malays, 47 Indians, and 24 Chinese. The mean age of patients was 58 years (range 16 to 92). The mean PA-to-tibial plateau distance was 9.9 mm for the right lower limb (range 2.5 mm to 17.2 mm) and 10.24 mm for the left (range 5.5 mm to 15.4 mm). There were no significant correlations between PA-to-tibial plateau distance with osteoarthritis grade, age, gender, and racial origin (P > 0.05); however, there was a positive correlation between PA-to-tibial plateau distances with popliteus muscle thickness (P = 0.000). Conclusion: Osteoarthritic condition in the knee does not reduce the popliteal artery to the tibial plateau distance. Hence, a higher osteoarthritic grade does not impose additional risks with regards to popliteal artery to tibial plateau distance, with relatively similar arterial injury risks compared to normal knees.